Eksplorasi dan identifikasi bakteri simbion wereng batang coklat (Nilaparvata lugens Stal.) sebagai pendegradasi insektisida imidakloprid - Sanjaya, Muhamad Sony; Fitriana, Yuyun; Lestari, Puji; Suharjo, Radix (Universitas Lampung, 2024)
Rice is an important food crop and a staple food source in Indonesia. The challenges in increasing rice production are not only caused by weather factors (drought, flooding) but also by pest and plant disease attacks. One of the rice pests that causes significant losses is the brown planthopper (BPH). Insecticides with the active ingredient imidacloprid have been known to effectively control brown planthoppers. However, in recent times, resistance to this insecticide has developed in brown planthoppers. This study aims to investigate the possible presence of symbiotic bacteria in brown planthoppers that can degrade imidacloprid insecticide as their carbon source. The steps taken include biochemical tests and testing the growth ability on media containing imidacloprid. The results of the tests showed that the bacterial isolates tested were unable to degrade the imidacloprid insecticide.